Chinese Youth’s Understanding and Practice of "Carbon Peak" and "Carbon Neutral" - Xiaofei Lai, Bin Zou (Forest Chemicals Review)
Climate change is a common challenge facing the global community. At the two sessions in 2021, "carbon peak" and "carbon neutral" were written into the Work report of the Chinese government for the first time. This shows that the Chinese government has placed the construction of ecological civilization high on the national development plan. And firmly pursue the purpose of harmonious coexistence between man and nature. The research group compiled a questionnaire "Chinese Youth Energy Conservation and Emission Reduction Questionnaire", distributed 1000 questionnaires, and received 939 valid questionnaires. It is found that most Chinese youth have a certain understanding of "carbon peak" and "carbon neutral" knowledge; In terms of the ideology of energy conservation and emission reduction,56.7percent of Chinese youth regard "conservation awareness", "environmental protection awareness" and "ecological awareness" as "very important", "important" and "somewhat important". It shows that Chinese youth have a general consciousness of energy conservation and environmental protection. In terms of energy conservation and environmental protection, the most common behavior adopted by Chinese youth is "saving water", followed by "giving priority to using transportation", "giving priority to using new energy transportation", "timely turning off electricity to reduce electricity consumption" and "saving meals". Research shows that Chinese youth are taking action to realize the concept of energy conservation and environmental protection.